Absolute and reverse mw-mile methods for cost allocation in a deregulated power system / Jeffri Jinal - Jinal, Jeffri (2003)
This paper introduces a methodology to allocate the costs among users in the power system by referring to the topological analysis of power flows in the transmission line. The methodology in cost allocation uses two types of MW-MILE method which are absolute and reverse approaches. Absolute MW-Mile approach cost is allocated in proportion to the ratio of apparent power flow and the line rating which ignores the direction of the power flow. Whereas, the Reverse MW-Mile approach cost is allocated in proportion to the ratio of reverse power flow and the line rating. The methods are capable to determine the network usage by any load and/or generator by cumulating all the allocated cost with respect to the load and/or generator bus. The cost allocation is analyzed by taking into account the existent conditions ofl1 given electric network and also during the effect of power transfer between areas. A case study of IEEE RTS for 9 bus, 24 bus, 57 bus and 118 bus is carried to evaluate the effectiveness of the MW-Mile methods in allocating the cost for each user or bus.